Kenya : Staff Report for the 2009 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2010)
This paper presents the staff report for Kenya's 2009 Article IV Consultation on economic development and policies. The progress Kenya achieved on the growth and poverty reduction fronts stalled in 2008 owing to a series of adverse developments, including the global economic crisis. The political situation is generally stable, but there appears to be constraining consensus on key issues. The spillover effect of the global financial crisis slowed export growth, tourism receipts, remittances, and private capital inflows.